Accounting and Billing in GPRS Data Network - Krisiūnienė, A.; Batkauskas, V. (Elektronika ir Elektrotechnika, 2005)
Billing and rating of GPRS technology is analyzed. Billing dependence on the quality of services, billing algorithms and billing accuracy is reviewed. The part of accounted data that is beneficial to the end-user is experimentally evaluated. Comparison of data measured by customer and network equipment is experimentally done. When using consumer software, a measuring error (the difference between the data obtained by the consumer and the detailed bill presented by the service supplier) is ±5%. Calculating the amount of transferred data consumer software cannot be used, because many additional features of consumer equipment cause accounting errors. Metrological verification of determination of the amount of transferred data for mobile data networks are described. Various differentiated charges appear therefore account adequacy should be guaranteed for the customer. Service providers should take care of inspection of transferred data measuring since mobile data services are getting more and more popular. Ill. 3, bibl. 6 (in Lithuanian; summaries in Lithuanian, English, Russian).